1991
DOI: 10.1093/ajcn/53.5.1275
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B − 6 deficiency impairs interleukin 2 production and lymphocyte proliferation in elderly adults

Abstract: The effect of vitamin B-6 deficiency on immune response was studied in eight healthy elderly adults. The protocol consisted of a 5-d baseline (BL) period; a vitamin B-6-depletion period of less than or equal to 20 d; three stages of vitamin B-6-repletion, each lasting 21 d; and a 4-d final phase. The amounts of vitamin B-6 ingested during the different phases of the study were 3.00, 15.00, 22.50, and 33.75 micrograms.kg body wt-1.d-1, respectively. During the final phase the subjects ingested 50 mg vitamin B-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(92 citation statements)
references
References 31 publications
4
86
1
1
Order By: Relevance
“…The supplementation was more effective in those subjects with the lowest initial plasma pyridoxal phosphate levels, indicating that higher than RDA levels of B6 might be needed to achieve optimal immune responsiveness in older persons. This is supported by the study by Meydani et al (122) who, using a B6 depletionrepletion protocol, showed that IL-2 production and mitogenic response to T and B cell mitogens by peripheral blood mononuclear cells of older subjects are influenced by changes in dietary vitamin B6 levels. In this study, biochemical measures of vitamin B6 status returned to normal at dosages of 1.90-1.96 mg/day.…”
Section: Vitamin B6supporting
confidence: 52%
“…The supplementation was more effective in those subjects with the lowest initial plasma pyridoxal phosphate levels, indicating that higher than RDA levels of B6 might be needed to achieve optimal immune responsiveness in older persons. This is supported by the study by Meydani et al (122) who, using a B6 depletionrepletion protocol, showed that IL-2 production and mitogenic response to T and B cell mitogens by peripheral blood mononuclear cells of older subjects are influenced by changes in dietary vitamin B6 levels. In this study, biochemical measures of vitamin B6 status returned to normal at dosages of 1.90-1.96 mg/day.…”
Section: Vitamin B6supporting
confidence: 52%
“…Low vitamin B 6 concentrations could thus reflect an increased consumption of PLP in the accelerated synthesis of cytokines (76) and in the activation and proliferation of lymphocytes, both of which are key events in the inflammatory process (77,78) . Considering the epidemiological evidence of a role of vitamin B 6 in inflammatory-related diseases and the observed relationship with inflammatory markers (11,16,18,79) , it is plausible that vitamin B 6 plays a role in CVD pathogenesis through mechanisms linked to inflammation (Table 4).…”
Section: Yesmentioning
confidence: 99%
“…Hussein et al (2008) also found a high CD4 þ /CD8 þ T-cell ratio in RA patients. Low plasma PLP concentrations have been related to alteration of immune responses, including impairment of both humoral and cell-mediated immunity (Meydani et al, 1991(Meydani et al, , 1992Rall and Meydani, 1993). In turn, reduced plasma PLP levels may alter immunological functions.…”
Section: Immune Responsesmentioning
confidence: 99%